A STUDY ON KNOWLEDGE AND ADOPTION OF IMPROVED SERICULTURAL TECHNOLOGIES IN MURSHIDABAD DISTRICT OF WEST BENGAL - SAHA, A.K.; SAHA, A.K.; SAIIA, A.B.; PANDIT, D.; BAJPAI, A.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
The study was undertaken in 14 villages of Murshidabad district of West Bengal with the objective to know the knowledge and adoption of recommended improved practices of both mulberry cultivation and silkworm rearing along with constraints faced by them. Survey was conducted among randomly selected 828 sericulturists by peronal interview method. Majority of sericulture farmers had knowledge on different practices of mulberry cultivation like improved mulberry variety (52%), spacing (5 1%), soil testing (63%), application of recommended dose of chemical fertilizer (5 1%) and leaf transportation and preservation (73%) while that of silkworm rearing practices were separate rearing house (88%), egg transportation (65%), regular bed cleaning (90%), use of bed cleaning with thread! net (52%), use of bed disinfectant with Labex 69%), bed spacing (68% and usé of recommended number of chandraki (66%). Majority of farmers’ knowledge though had high in many improved technologies! practices recommended for mulberry cultivation and silkworm rearing, but the percentage of adopter was less as expected. Overall, lower sale value of end product was the most important cause considered by almost all the famers. Besides, Lack of finance, input support, awareness and impact of traditional practice were the few majors constraints felt by the sericultural farmers. The major constraints in adoption of mulberry cultivation practices were impact of traditional practices and small land holding capacity, lack of input support system, awareness and financial conditions of the farmers. Similarly, impact of traditional practice, lack of finance, awareness and low cocoon price was the major constraints felt by the farmers in adopting silkworm rearing technologies.